Microtremor Assessment to Investigate the Local Site Response and the Depth of Weathering Rock at Institut Teknologi Sumatera Campus Area - Maria Rosalita Pujiastuti Sudibyo; Erlangga I. Fattah; Cahil Suhendi; Reza Rizki (Natural B, Journal of Health and Environmental Sciences, 2019)
Local site effects related to the local geology can influence the damage of earthquake, by amplifying or deamplifying the horizontal movement of ground motion. To characterize the site effects in a local area, the natural frequency and the amplification factors can be estimated by performing Horizontal-to-Spectral Ratio on microtremor data. The amplification factors and natural frequency obtained then can be used to estimate the seismic vulnerability and the depth of the bedrock. This method is applied by recording the microtremor data in 1.5x1.5 km2 ITERA campus area, deploying 11 points of measurements. The recording of 45 to 60 minutes long for each point has been done to accommodate the lowest possible natural frequency we may obtain. The HVSR estimation shows that there are two predominant frequency, F0 and F1, ranging from 0.7 to 1.31 Hz and 3.88 to 8,71 Hz. These two dominant frequencies are associated with two layers of tuff, a soft weathered laying on a thicker and stiffer tuff rock layer. The amplification factors Ao are varied from 2.5 to 9 and is considered as the low bound of the real amplification factor. The depth of the soft weathered tuff is estimated ranging from 8 to 18 m. The seismic vulnerability estimated from this research is ranged from 7 to 65, implying that the area has mid-level of vulnerability.